Challenges experienced by school-based mentor teachers during initial teacher training in five selected schools in amathole east district - Baartman, Nomakhaya (Penerbit Universiti Kebangsaan Malaysia, 2020)
All teacher education institutions depend on school-based teachers to mentor and guide studentteachers on Teaching Practice (TP). Student teaching has been called the most challenging, critical and rewarding stage of teacher education. School-based mentor teachers have a great influence on the development of student-teachers’ orientation, conceptions and classroom practice. Although there are benefits in TP for both student teachers and mentor teachers, they might be overshadowed by the conditions under which the school-based mentor teachers work. Hence, this study evaluates the challenges experienced by school-based mentor teachers in supporting Initial Teacher Training (ITT). The study adopted a qualitative case study design in which a purposeful sample of 5 schoolbased mentor teachers participated. Semi-structured interviews were conducted as the main and sole data collection tool. Content analysis was used to analyse data thematically. From the findings of the study the challenges seemed to outnumber the benefits of mentoring to school-based mentor teachers. Furthermore, based on the collected data, I conclude and recommend that there should be introduction of mentor training programmes, mentors be given incentives and have reduced workload in order to have an improved and effective mentoring process.